A fetus at risk for congenital adrenal hyperplasia - Spagnolo, Antonio G.; Di Pietro, Maria Luisa (Medicina e Morale, 1990)
The authors discuss the case study of a 21-years-old pregnant woman whose first child was a boy with a congenital adrenal hyperplasia due to a 21-hydroxylase deficiency. During the eighth week of her pregnancy she was treated with glucocorticoids, because of the risk that the fetus might be affected by the same disease as the other child. The therapy was continued after confirmation of the disease by prenatal diagnosis with chorionic villus sampling (CVS) at the 10th week. Three ethical issues are considered in the article: 1) the acceptability of the risks connected with the CVS; 2) the risk/benefit ratio for the fetus and mother with reference to the therapy carried out; 3) the effects of a beginning of the treatment after a less dangerous and more effective late prenatal diagnosis by amniocentesis. Finally the authors present their personal view on decision-making in a case like this one.